Ectopic ureteral opening clinical assessment of 13 cases - Takaba, H (Hinyokika kiyo. Acta urologica Japonica, 1989)
Thirteen cases of ectopic ureteral opening, surgically intervened during the past 10 years, were reviewed regarding the patients profiles, diagnostic procedure, treatment and concomitant anomalies. The diagnostic procedures are consisted of the conventional methods such as an intravenous urography, a vaginography, and a renoscintigraphy, which are important to identify and locate the immature kidney or the kidney with duplication anomaly. An angiographic examination is to be abandoned because it is invasive and rather insensitive. The surgical treatment should be determined depending on the renal function remained, ureteral morphology and the site of the ureteral opening